Haemorrhagic septicaemia of cattle & buffaloes in Asia - Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2013)
Haemorrhagic septicaemia is a disease affecting buffaloes and cattle that occurs mostly in Asia, particularly in the Southeast Asia. It is quite prevalent in Africa, Middle East and occasionally in southern Europe. In Asia, the disease has been reported in Malaysia, Thailand, Philippines, Indonesia, Vietnam, Laos, Cambodia, Myanmar, India, Sri Lanka and Pakistan. It occurs mostly as outbreaks during periods of environmental stress. It is a long-held belief that haemorrhagic septicaemia occurs during the monsoon season and during paddy planting period when buffaloes are in very stressful situations. The disease affects mainly cattle and buffaloes, but the latter are known to be more susceptible to the disease than cattle, killing an average of 360 heads of cattle and buffaloes a year in Malaysia, approximately 1,000 heads in the Philippines, Myanmar and Cambodia, 600 heads in India and 285 heads in Sri Lanka. There is no doubt that outbreaks of haemorrhagic septicaemia lead to a devastating effect to livestock industry. This book is aimed as guide for students studying veterinary and animal sciences, veterinarians and scientists dealing with cattle and buffaloes particularly in countries where haemorrhagic septicaemia is reported. This book compiles, describes and analyses literatures on haemorrhagic septicaemia in Asia. Since haemorrhagic septicaemia is a disease of Asian countries; literatures in established journals are extremely rare.